Conceptualizing Organizational Commitment and Knowledge Sharing on Organizational Citizenship Behavior: Property Industries Case - Soelton, Mochamad; Nurullah, Tubagus Muhammad Fajrin; Yuliantini, Tine; Anah, Sri; Paijan; Kuswibowo, Christian (ARE Publisher, 2024)
Purpose – This study aims to examine and analyze the effect of Organizational Commitment and Knowledge Sharing on Organizational Citizenship Behavior Mediated by Job Satisfaction. Methodology – This study uses a saturated sample of 40 employees. Quantitative analysis used the questionnaire collection method, using the Smart–PLS Structural Equation Model analysis method. Findings – Organizational Commitment and Knowledge Sharing have a positive effect on Organizational Citizenship Behavior, Organizational Commitment and Knowledge Sharing have a positive effect on Job Satisfaction, Job Satisfaction has a positive effect on Organizational Citizenship Behavior, Job Satisfaction is able to mediate Organizational Commitment has a positive effect on Organizational Citizenship Behavior, Job Satisfaction is able to mediate Knowledge Sharing has a positive effect on Organizational Citizenship Behavior. Authenticity – This research examined OCB, which has a broad and significant impact on company performance. It also provides better comprehension concerning the relationship of spiritual leadership, self-efficacy, locus of control, and job satisfaction on this indicator.